2006
DOI: 10.2224/sbp.2006.34.5.557
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Consumerism and Lifestyle as Correlates of a Voluntary Simplicity Lifestyle

Abstract: Data from a questionnaire were collected from 189 Japanese female undergraduates at a women's university. They were 18, 19, or 20 years of age. The measures included a 22-item 7-point voluntary simplicity lifestyle scale, a 9-item 5-point scale of the evaluation of a voluntarily simple life, an 11-item 4-point scale of environmentally responsible consumerism and a 28-item 5-point scale of a nonsimplicity lifestyle. Factor analysis was conducted for each scale and Cronbach's αcoefficients were calculated for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 7 publications
2
48
0
18
Order By: Relevance
“…In the present study, the "Environmentally Responsible Consumerism Scale" was prepared based on Iwata (2002), the "Voluntary Simplicity Lifestyle Scale" was prepared based on Iwata (2006), and the "Consumption Values Scale" was prepared based on Lin and Huang (2012). It is argued in some studies that those adopting novelty do not engage in environmentally responsible consumerism.…”
Section: Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…In the present study, the "Environmentally Responsible Consumerism Scale" was prepared based on Iwata (2002), the "Voluntary Simplicity Lifestyle Scale" was prepared based on Iwata (2006), and the "Consumption Values Scale" was prepared based on Lin and Huang (2012). It is argued in some studies that those adopting novelty do not engage in environmentally responsible consumerism.…”
Section: Methodsmentioning
confidence: 96%
“…Cowles and Crosby (1986) argued that voluntary simplicity is composed of the dimensions of material simplicity, self-determination, and ecological awareness. Iwata (1997Iwata ( , 2002Iwata ( , 2006 suggested that voluntary simplicity lifestyle can be examined in three sub-dimensions: cautious attitudes in shopping, acceptance of self-sufficiency, and a desire for a voluntarily simplicity life. Ozgul (2011), on the other hand, stated that a voluntary simplicity lifestyle has four dimensions: product feature, material life, planned shopping, and selfsufficiency.…”
Section: Literature Review 21 Voluntary Simplicity Lifestylementioning
confidence: 99%
See 3 more Smart Citations